Pengaruh Locus Of Control Dan Kepemimpinan Terhadap Kinerja Karyawan PT. Pegadaian Cibadak - Leofani Deris; Faizal Mulia Z; Sopyan Saori (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
PT Pegadaian Cibadak is a State-Owned Enterprise company engaged in financial institutions that provide credit to the public with movable goods as collateral. In this company there is an influence of locus of control on employee performance which causes a decrease in targets on employee performance, besides that there are several attitudes of leaders who feel unfair in terms of promotion and leaders also pay less attention to the conditions where employees work when working which causes a decrease in employee performance. The purpose of this study was to analyze the effect of locus of control, and leadership on employee performance. The research method used is an associative descriptive analysis method with a quantitative approach. The data collection techniques used are observation, interview, questionnaire, documentation, and literature study. The population in this study were employees of PT Pegadaian Cibadak with a sample size of 34 people using non-probability sampling techniques. Measurement in this study uses semantic differential. Furthermore, the data obtained with various tests to answer the hypothesis in this study. The results of this study indicate that there is a positive and significant influence on the performance of employees.